PERANCANGAN SISTEM KONTROL MESIN SCOWAS BERBASIS IOT PADA KANDANG AYAM BROILER - Salmon, Ersa Agnes; Hijriatullah, Rizal Umarhandi; Swamardika, Ida Bagus Alit; Wijaya, I Wayan Arta (Jurnal TAM (Technology Acceptance Model), 2024)
This study examines the design of an IoT-based SCOWAS (Smart Coop Warming System) control system for broiler chicken coops using Arduino Mega, DHT 22 sensor, thermocouple, ThingSpeak platform, and Telegram bot. The main goal of this system is to automate the control of temperature and humidity in broiler chicken coops, thereby improving maintenance efficiency and chicken welfare. Arduino Mega serves as the main controller, collecting data from the DHT 22 sensor to measure temperature and humidity, as well as from the thermocouple for more accurate temperature monitoring. The collected data is then sent to the ThingSpeak platform for real-time monitoring and analysis. Additionally, this system is integrated with a Telegram bot that notifies farmers about the environmental conditions of the coop, such as temperature and humidity that do not meet the set thresholds. The implementation of this system allows for more responsive and measured control of coop environmental conditions, minimizing manual interventions that could disrupt productivity. Testing results show that this system is capable of providing accurate and real-time information and control in both measurement and communication with IoT, thus supporting the improvement of broiler chicken maintenance quality and efficiency, and offering an effective and innovative solution in the modern livestock industry.